Activities at the Wagah Border: Perspectives on National Security, Sociology of Law, and Military Law - Arief Fahmi Lubis (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This community service-based empirical study examines activities at the Wagah Border through the integrated perspectives of national security, sociology of law, and military law. Using participatory field observation, structured interviews with military personnel and visitors, and qualitative document analysis, the research explores how ceremonial and security practices function as instruments of state sovereignty, legal order, and social regulation. The findings indicate that the Beating Retreat Ceremony operates not merely as a symbolic performance but as a structured security mechanism governed by hierarchical command, regulated force expression, and institutional accountability. Patterns of public compliance and coordinated inter-agency control reflect the internalization of legal norms within both military institutions and civilian audiences. The border space thus emerges as a socio-legal arena where national identity, deterrence signaling, and rule-based discipline converge in a controlled yet highly performative environment. The study demonstrates that military law and security governance at Wagah contribute to regional stability by institutionalizing order, reinforcing legal legitimacy, and fostering civic awareness of state authority within a geopolitically sensitive boundary zone.